Long‐term depression incidence and associated mortality among African American and White prostate cancer survivors. Issue 18 (1st June 2021) - Parikh, Ravi B.; Gallo, Joseph J.; Wong, Yu‐Ning; Robinson, Kyle W.; Cashy, John P.; Narayan, Vivek; Jayadevappa, Ravishankar; Chhatre, Sumedha
Abstract : Background: Depression is common after a diagnosis of prostate cancer and may contribute to poor outcomes, particularly among African Americans. The authors assessed the incidence and management of depression and its impact on overall mortality among African American and White veterans with localized prostate cancer. Methods: The authors used the Veterans Health Administration Corporate Data Warehouse to identify 40, 412 African American and non‐Hispanic White men diagnosed with localized prostate cancer from 2001 to 2013. Patients were followed through 2019. Multivariable logistic regression was used to measure associations between race and incident depression, which were ascertained from administrative and depression screening data. Cox proportional hazards models were used to measure associations between incident depression and all‐cause mortality, with race‐by‐depression interactions used to assess disparities. Results: Overall, 10, 013 veterans (24.5%) were diagnosed with depression after a diagnosis of prostate cancer. Incident depression was associated with higher all‐cause mortality (adjusted hazard ratio [aHR], 1.27; 95% confidence interval [CI], 1.23‐1.32). African American veterans were more likely than White veterans to be diagnosed with depression (29.3% vs 23.2%; adjusted odds ratio [aOR], 1.15; 95% CI, 1.09‐1.21). Among those with depression, African Americans were less likely to be prescribed an antidepressant (30.4% vs 31.7%; aOR, 0.85; 95% CI, 0.77‐0.93). The hazard of all‐cause mortality associated with depression was greater for African American veterans than White veterans (aHR, 1.32 [95% CI, 1.26‐1.38] vs 1.15 [95% CI, 1.07‐1.24]; race‐by‐depression interaction P < .001). Conclusions: Incident depression is common among prostate cancer survivors and is associated with higher mortality, particularly among African American men. Patient‐centered strategies to manage incident depression may be critical to reducing disparities in prostate cancer outcomes. Abstract : Compared with non‐Hispanic White US veterans, African American veterans with localized prostate cancer and no preexisting depression are more likely to be diagnosed with depression after their diagnosis but are less likely to be prescribed antidepressant therapy. Among prostate cancer survivors with depression, the association between depression and mortality is higher among African American veterans than non‐Hispanic Whites.